Transformasi Pemasaran Melalui Pemanfaatan Media Sosial - Andrean Sukoco, Sampir; Nisak , Chonitatun; Novita Sari , Devi (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
The development of digital technology has created significant opportunities for MSME actors to enhance business stability, expand market reach, and improve operational cost efficiency. However, many business owners have not yet utilized digital technology optimally, including Kedai Alee, a home-based business in Sukorambi District that produces various traditional and modern cakes. The community service activities were carried out through several methods, including initial problem observation, creation of social media accounts, digital marketing training, periodic monitoring, and evaluation. The results of this program show that the partner now has active social media accounts and is able to apply digital marketing. This is reflected in the improved ability of Kedai Alee to manage its Instagram, Facebook, and TikTok accounts, thereby expanding its marketing reach